Contrasting perceptions of male and female dental students regarding smile aesthetics based on their gingival display - Yessy Josephine Sijabat; C. Christnawati; Dyah Karunia (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2018)
Background: Perception consists of personal opinion in relation to an object. In terms of aesthetics, perception normally differs from one individual to another based on several factors such as gender. When expressing emotion, a smile is the most important facial expression whose aesthetics are constructed from a number of components, including gingival display. Purpose: This study aimed to establish the comparative perceptions of the smile aesthetics of male and female dental students based on their gingival display. Methods: 36 dental students, divided equally according to gender, were enrolled in this study. Photographic images of the smile of each subject were taken from a frontal direction with a Canon EOS 700D digital camera and subsequently printed. Assessments were conducted by comparing the photographs of subjects from the perspective of smile references based on the gingival display, followed by subject scoring on the basis of smile classification. Assessments were conducted twice within a two-week period to confirm test reliability. The data collected was analyzed by means of kappa statistic and U-Mann Whitney tests. Results: The test results indicated that all subjects demonstrated a coincidence in their analysis (κ=0.84). Statistical analysis showed that a score of 0.902 (p>0.05) had been produced by a U-Mann Whitney test. Conclusion: It can be concluded that no difference exists between male and female students in the perception of smile aesthetics based on the gingival display.